PENGEMBANGAN APLIKASI ENCODE DAN DECODE TREE MENGGUNAKAN BLOB CODE - Astria Hijriani; Wamiliana Wamiliana; Ady Candra (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2014)
Tree Structure is used widely to represent problems in daily life, especially in computer science and technology. One method that is used to represent a tree is Blob Code. In this research, we developed an application to Encode and Decode Tree using Blob Code. This application aims to simplify the process of changing tree into a blob code (encode) and the process of changing Blob code into the form of tree (decode).Â Keywords: Encode, Decode, Tree, representation Tree, Blob Code.